Discovery of common variants associated with low TSH levels and thyroid cancer risk - Gudmundsson, Julius (2012)
To search for sequence variants conferring risk of nonmedullary thyroid cancer, we focused our analysis on 22 SNPs with a P < 5 × 10(−8) in a genome-wide association study on levels of thyroid stimulating hormone (TSH) in 27,758 Icelanders. Of those, rs965513 has previously been shown to associate with thyroid cancer. The remaining 21 SNPs were genotyped in 561 Icelandic individuals with thyroid cancer (cases) and up to 40,013 controls. Variants suggestively associated with thyroid cancer (P < 0.05) were genotyped in an additional 595 non-Icelandic cases and 2,604 controls. After combining the results, three variants were shown to associate with thyroid cancer: rs966423 on 2q35 (OR = 1.34; P(combined) = 1.3 × 10(−9)), rs2439302 on 8p12 (OR = 1.36; P(combined) = 2.0 × 10(−9)) and rs116909374 on 14q13.3 (OR = 2.09; P(combined) = 4.6 × 10(−11)), a region previously reported to contain an uncorrelated variant conferring risk of thyroid cancer. A strong association (P = 9.1 × 10(−91)) was observed between rs2439302 on 8p12 and expression of NRG1, which encodes the signaling protein neuregulin 1, in blood.